Anne Nørgård Jørgensen and Birthe L. Clausen (eds.): Military Aspects of Scandinavian Society in a European Perspective, AD 1-1300. Papers from an International Research Seminar at the Danish National Museum, Copenhagen, 2-4 May 1996 (Nationalmuseet, 1997 - Poulsen, Bjørn (Historie/Jyske Samlinger, 2000)
Anne Nørgård Jørgensen and Birthe L. Clausen (eds.): Military Aspects of Scandinavian Society in a European Perspective, AD 1-1300. Papers from an International Research Seminar at the Danish National Museum, Copenhagen, 2-4 May 1996. Publications from the National Museum, Studies in Archaeology & History, Vol. 2. (Nationalmuseet, 1997). 266 s., 295 kr.